MANAJEMEN PEMELIHARAAN DAN PERAWATAN GEDUNG PADA RUMAH SAKIT PRATAMA KECAMATAN LEIHITU KABUPATEN MALUKU TENGAH - Ole, Septiana; Lenora Leuhery; La Mohamat Saleh (Journal Agregate, 2024)
Research to analyze Building Maintenance and Maintenance Management at Pratama Hospital, Leihitu District, Central Maluku Regency, before the damage to buildings and fittings is heavier and disrupts services to the community, it is necessary to have good maintenance so that the planned technical life can be achieved. where there are 5 components, namely Structural, Architectural, Electrical, Mechanical and Outdoor Layout. The study was conducted by distributing questionnaires, the data analysis technique used was SPSS 26 software. Data analysis starts with validity tests and reliability tests with statistical descriptive analysis methods. This research was conducted to determine the assessment of building users and the implementation of building maintenance and maintenance. From the results of the analysis conducted on building user ratings, descriptive analysis showed that of the 30 respondents and 3 categories with the highest frequency. Based on structural variables, 15 people rated "good enough" architectural variables, 21 people rated "good enough", electrical variables 20 people rated "good enough, mechanical variables 21 people rated "good enough", outdoor spatial variables 20 people rated "good enough", and housekeeping variables 21 people rated "good enough". It is known that the results of the implementation of building maintenance and maintenance based on the category with the highest percentage, namely the "good enough" category, including 50% structural variables.